Argumentation in medical specialized advertisements: the case of a radiological contrast media. - Mendoza Puertas, Jorge Daniel (Círculo de Lingüística Aplicada a la Comunicación, 2013)
This paper offers an argumentative approach from a linguistic point of view to a type of discourse: direct-to-doctor advertising discourse. A specific advertisement taken from a sanitary center is analyzed, showing its particular mechanisms aiming to persuade an expert addressee.
Keywords: advertising; argumentation; medicine; radiology.